Analisis Perbandingan Semantik Pada Kata يَحْكُمْ dan حُكْمٌ pada Surat Al-Maidah Terjemahan Depag Dengan H.B. Jassin - Diki Cahyo Ramadhan; NURUL HIDAYAH; Isniyatun Niswah Muflikhatuz (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study discusses the comparative analysis of the meaning of the word يَحكُمْ andحُكْمٌusing the translation of the Ministry of Religion and H.B. jassin. And the method used is thelibrary research method. In Arabic the word law has no equivalent. Word translation يَحكُمْ andحُكْمٌin the Qur'an of the Ministry of Religion with H.B. Jassin is quite accurate in terms of the Indonesian language level. Although there are slight differences between the translations of H.B. Jassin with the translation of the Ministry of Religion. H.B. translation Jassin is translated literally with a poetic nuance, while the MoRA translation is translated freely. Therefore, these two translations do not reduce the accuracy of the translation results. The author draws the conclusion, that the translation of H.B. Jassin and the Ministry of Religion in the Al-Qur'an letter al-Maidah in the first verse to the fiftieth verse are quite accurate in terms of the Indonesian language level. Keywords : Analysis, Word comparison يَحكُمْ andحُكْمٌ, Translation of the Ministry of Relegion and H.B. Jassin